Drug Abuse Among Youths In Eswatini: Causes And Possible Intervention Strategies - Dr. Phumuzani Mpofu; Vilakati Abel; Machingauta Tatenda Thelma (Journal of Research in Social Sciences, 2025)
The escalating prevalence of drug abuse among youths in Eswatini poses a significant threat to development, education, and public health, reflecting broader trends in Southern Africa. Despite increased attention on the rising prevalence of drug abuse in Africa, limited qualitative research captures the lived experiences and contextual factors of drug abuse among youths in Eswatini. To address this gap, this research explored the determinants of drug abuse among youths, identified drug types, and informed context-specific prevention strategies. A phenomenological approach, grounded in the interpretivist paradigm, was adopted to enhance the appreciation of participants’ multiple realities. Semi-structured interviews with youths and a focus group discussion with parents were conducted for data collection. Reflexive thematic analysis revealed individual, home, school, sociocultural, and environmental factors as determinants of drug abuse. Notably, the study identified Lea and Rocky as emerging drugs of concern. Parental inclusion illuminated holistic insights into home and societal influences in multilevel interventions. Findings propose targeted training and education, community-based interventions, and national-level initiatives. Conclusively, drug abuse is multifaceted, which is critical for stakeholders designing Eswatini context-specific interventions